A new program for systematically enhancing cognitive reserve in healthy adults: A pilot randomized active-controlled clinical trial - Carol Kotliar; Lisandro Olmos; Martín Koretzky; Ricardo Jauregui; Tomás Delía; Oscar Cingolani (PLoS ONE, 2025)
Objective To evaluate the effectiveness of the Mental Training Tech 24.5 (MTT24.5) cognitive stimulation program, designed to enhance cognitive performance and neuroplasticity in healthy adults. Background Cognitive decline is a significant concern in aging populations, with research suggesting that neuroplasticity and cognitive reserve can be enhanced through targeted cognitive training. The MTT24.5 program aims to stimulate brain function through a combination of new knowledge acquisition (DATA) and learning techniques (TECHS), organized into a systematic algorithm. This approach may offer a novel way to prevent or mitigate age-related cognitive decline. Design Pilot clinical study, active-controlled, open randomization. Setting Adults from the general population with no clinical cognitive deterioration, recruited from three sites within the Autonomous City of Buenos Aires and its metropolitan area. Participants 120 volunteers were enrolled, of which 76 participants (56 in the intervention group, 20 in the control group) met the study requirements and selected a site closest to their residence. Methods The MTT24.5 program consists of 12 weekly in-person sessions (totaling 24.5 hours), during which participants learned 40 knowledge units (DATA) and 100 learning techniques (TECHS). These were organized into binomials, where each unit of DATA was paired with 3–4 TECHS. Pre- and post-intervention assessments included medical history, lifestyle factors, cognitive reserve scale, Addenbrooke’s Cognitive Examination-Revised (ACE-R), and Mini-Mental State Examination (MMSE). Results The mean age was 59 years for both groups. Baseline ACE-R scores were comparable (91.3). The global cognitive score increased by 4.6 points (5%) in the intervention group compared to a decrease of 0.5 points in the control group (p < 0.001). The most significant improvement was observed in the memory domain (2.4 points, 11.4% increase) versus a 0.3-point increase in the control group (p < 0.007), with secondary improvements in verbal fluency, language, and visuospatial skills. Notably, participants with baseline ACE-R scores below 85 showed greater improvements (p < 0.003). The effects were consistent across various phenotypic factors, such as age, sex, chronic disease distribution, and lifestyle. Conclusions The MTT24.5 program, based on a systematic algorithm for acquiring new knowledge and skills, significantly enhances cognitive reserve and overall cognitive performance, particularly in individuals with lower baseline cognitive scores. These findings suggest that structured cognitive stimulation could play a critical role in preventing cognitive decline and promoting cognitive health in healthy adults. Given the promising results, future studies involving larger populations and long-term follow-up are essential to validate these effects and explore the potential for mitigating age-related cognitive decline and enhancing quality of life. Registration The study was registered in accordance with local regulations at the National Council for Scientific and Technological Research (CONICET) – Institute of Biomedical Research (BIOMED), and also in the National Ethics Committee, and at clinicaltrials.gov (NCT06549517).